Punjab borderland : mobility, materiality and militancy, 1947-1987 - Chattha, Ilyas (Cambridge Cambridge University Press, 2022)
The Punjab Borderland offers a fascinating insight into how the new international boundary between India and Pakistan was made, subverted, and transformed. Dispelling the established historiographical narratives of an increasingly militarised border that presents as the epitome of animosity and a classic example of inter-state tension, this book offers a corrective to these accounts by bringing out narratives of border crossings and social relations built on mutual benefit and trust. It conceptualises the making of the vast contraband as an analytical tool, not merely as borderland societies' modes for evading the state imposition of a partitioned geography on their local lifeworld, but as a catalyst for enabling social mobility and political empowerment for the population involved and a thriving market for consumption in the urban centres. It reveals a 'bottom-up' history of the Punjab border and the invention of the borderland society, narrating a story with local meanings and transnational dimensions.
Keywords: India-Punjab; Pakistan